2009
DOI: 10.1002/poc.1609
|View full text |Cite
|
Sign up to set email alerts
|

Preferential mode of cyclization of tetrahydrofuran amino acids containing peptides: some theoretical insights

Abstract: Theoretical insights have been provided for the observed preference of cyclodimerization over intramolecular cyclization reactions in linear tripeptides containing “2,5‐cis” (2S,5R)‐tetrahydrofuran amino acid as well as in those containing “2,5‐trans” (2S,5S)‐tetrahydrofuran amino acid, using quantum chemical methods. The geometries of species involved as well as the feasibility of cyclization reactions are studied at the B3LYP/6‐31G(d,p) level of theory in gas phase as well as in solvent phase. Thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Indeed, at 6-311+G(d,p), 6-311++G(d,p), aug-cc-pVDZ, cc-pVTZ levels of basis set using B3LYP functional and at MP2/6-31G(d,p) level of theory, it is negative. These observations support our earlier predictions on the reactions based on B3LYP/6-31G(d,p) level of theory in the gas phase [45]. In summary, the qualitative trends of the energies of the intermediates, transition states and products in a given reaction pathway are independent of the quality of the basis set used.…”
Section: Thermodynamic and Kinetic Aspectssupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, at 6-311+G(d,p), 6-311++G(d,p), aug-cc-pVDZ, cc-pVTZ levels of basis set using B3LYP functional and at MP2/6-31G(d,p) level of theory, it is negative. These observations support our earlier predictions on the reactions based on B3LYP/6-31G(d,p) level of theory in the gas phase [45]. In summary, the qualitative trends of the energies of the intermediates, transition states and products in a given reaction pathway are independent of the quality of the basis set used.…”
Section: Thermodynamic and Kinetic Aspectssupporting
confidence: 88%
“…Extensive NMR techniques (NOESY), classical molecular dynamics (MD), circular dichroism (CD) and mass spectrometric analyses proved this phenomenon. This led us to investigate the stabilities of the cyclic C 2 symmetric hexapeptides and cyclic tripeptides based on density functional theory (DFT) [44] calculations, and we found that cyclic hexapeptide products are thermodynamically more stable than cyclic tripeptides [45].…”
Section: Introductionmentioning
confidence: 99%
“…Peptides 1-4 were synthesized by cyclodimerization 7 (BocNH)-Phe-Leu] 2 , coupling with RCO-Lys(Boc)-OH and final deprotection gave the desired peptides. Peptides 1-3 were attached to the gold nanoparticles through place exchange reaction with octanethiol stabilized gold nanoparticles and the resulting conjugates could be visualized in their TEM pictures taken in MeOH and aqueous solution of peptide 1 attached nanoparticles (Fig.…”
Section: Resultsmentioning
confidence: 99%